(3cJGH aj GdbQGAGJs ((3eMeO Hf YHO GdNGdb Hf YHO GdQRGb Hf YHO GdNGdb GdeDPfs)
(3ChdgG (B:s
(3JYdehf HeDefjf eLQejf Hfi ESQGFjd HfcKhf GdbQGAGJ hJhLjgGJgG bQC (B( (3CdeU (B) (3HGdScJ Ydi cd MQa efgG cZjQgG ef ahGJM GdShQ s
(3BNQgG (B:s
(3Gdhba hGdEHJOGA BNQ GdHSedI e (B" (3HQH GdfGS (B" (3f dCf GdJGdi YWa HjGf dg aEf (B" (3GdeQH (B" (3bO dGjchf eGdckG hGdeGdc bO dGjchf EdgkG hGdfGS e hUdi Gddg Ydi SjOfG eMeO s
(3HgG fXGe GdJYbjHIs
(3cJHJ ahGJM GdCHhGH hGdShQ hQehR Gdhba hGdEHJOGA HeOGO CMeQs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdbQGAGJ hGdJLhjOs